Dietary and Nondietary Triggers of Oral Ulcer Recurrences in Behçet's Disease. Issue 9 (29th August 2017) - Volle, Geoffroy; Fraison, Jean‐Baptiste; Gobert, Delphine; Goulenok, Tiphaine; Dhote, Robin; Fain, Olivier; Gonzalez‐Chiappe, Solange; Lhote, François; Papo, Thomas; Thuillier, Aurélie; Rivière, Sophie; Mahr, Alfred
Abstract : Objective: The nature and impact of food and other external triggers in recurrences of Behçet's disease (BD)‐related oral ulcers (OUs) remain unknown. This survey investigated dietary and nondietary triggers of BD‐related OU recurrences. Methods: Patients with BD who were followed in 7 French hospital departments completed a self‐administered patient questionnaire. General and specific dietary triggering factors were sought in open questions. The questionnaire also included closed questions, notably to evaluate the effect of 6 general triggering situations and 24 selected foods. The results were expressed as number (percentage) of positive responses. Results: Among the 101 questionnaires distributed, 81 were usable. Among the 81 patients, 96% fulfilled the International Criteria for Behçet's Disease classification criteria, and 53% qualified their OU recurrences during the previous 12 months as very discomforting or discomforting. For the 6 general situations suggested, 50 patients (62%) declared ≥1 as a "sure" trigger of OU recurrences. In both open and closed questions, the most frequent triggers were fatigue/stress (37–47% of patients) and food (32–35%). Among the 24 suggested foods, nuts (48%), pineapple (42%), peanuts (32%), Emmental cheese (30%), almonds (23%), lemons (22%), and other cheeses (21%) were the most frequently reported. The corresponding open question gave consistent findings but with lower frequencies. Conclusion: Most patients can identify triggers of recurring BD‐related OUs, with fatigue/stress and food representing the most frequent triggers. The management of OU must consider such external factors. The histamine‐rich or ‐liberating properties of the commonly cited OU‐triggering foods suggest a hyperreactivity mechanism.